Are the western media really that interested in China? - Sparks, Colin (Javnost (Ljubljana), 2003)
This article considers the evidence about the strategic orientation of major western media companies on the Chinese market. It begins by proposing a typology of influence drawn from the analysis of post communist media change in Central and Eastern Europe. The evidence from there does not support the view that major media companies directly took over the media systems. It then reviews the evidence of the intentions of major media corporations and finds that, contrary to popular supposition, very few of them have any major commitments, at least as yet. Only News Corporation can be said to have a major involvement in the Chinese market. The article then reviews the possible reasons for this, including the nature and size of the current Chinese market. In particular, it shows that although the Chinese market is very large, and wealth is growing fast, it remains poor and the advertising revenues available are not yet substantial. On the basis of these findings and analysis, it is suggested that, contrary to popular views, it is unlikely that, in the near future, there will be any major foreign attempt to enter the mass market in Chinese television
Keywords: Kitajska; mass media; množični mediji; medijski trg; tuji kapital